Problematika Hafalan Juz 'Amma: Studi Kasus Santri Kelas 2 Madrasah Diniyah Pondok Pesantren An-Nur 2 Malang - Farhan Muzakki Fakhridana; Siti Nur Azizah; Annisa; Sabrina Nur Haliza (Aksioreligia, 2026)
The cognitive load problem was experienced by 2nd grade students of Madrasah Diniyah Pondok Pesantren An-Nur 2 Malang, showed by a decrease in the quality of Juz 'Amma memorization due to physical and mental fatigue. This study aims to analyze psychological problems in the process of memorizing Juz 'Amma and examine the effectiveness of psycho-pedagogical interventions in solving problems. This research method uses a qualitative approach with a case study method. The data source was determined through the purposive sampling technique, which involved students and tahfizh teachers. Data collection techniques were carried out comprehensively through participant observation, in-depth interviews, and documentation studies. Furthermore, the data were analyzed using interactive models (Miles, Huberman, and Saldana) which included the stages of data condensation, data presentation, and conclusion drawn, and tested for validity using triangulation of sources and techniques. The results of the study show that the difficulty in memorizing students purely stems from cognitive fatigue which triggers a decrease in motivation. To overcome this, psycho-pedagogical synergy has proven to be effective through external scaffolding of teachers (Talaqqi and Sim'i methods) and internal strategies of students (Wahdah method). In conclusion, memorization barriers are an accumulation of psychological and neurobiological factors that require adaptive handling. This study recommends a paradigm shift towards Differentiated Learning through the provision of halaqah zones and silent zones so that pedagogical interventions are more humane and on target.